The influence of biological maturity and competitive level on isometric force-time curve variables and vaulting performance in young female gymnasts - Moeskops, S.; Oliver, J. L.; Read, P. J.; Cronin, J. B.; Myer, G. D.; Haff, G. G.; Lloyd, R. S. (The Journal of Strength and Conditioning Research, 2020)
This cross-sectional study investigated isometric force-time curve variables and vaulting performance in young female gymnasts of varying maturity and competitive levels. One hundred twenty gymnasts aged 5-14 years were subdivided into maturity groupings and also according to their competitive level. Subjects performed isometric midthigh pulls (IMTP) before completing straight jump vaults that were recorded using two-dimensional video. All significance values were accepted at p < 0.05. Absolute peak force (PF abs) and force at various time epochs were significantly greater in more mature gymnasts, although no significant differences were observed in relative peak force (PF rel). When grouped by competitive level, elite gymnasts produced a significantly greater absolute rate of force development (RFD abs) at 0-150, 0-200, and 0-250 ms as well as relative RFD (RFD rel) at 0-200 and 0-250 ms than recreational gymnasts. Based upon regression analyses, force at 50 ms during the IMTP test explained 15% of vertical takeoff velocity during vaulting. Biological maturation seems to impact isometric force-time curve characteristics in young female gymnasts, and higher-level gymnasts produce greater RFD than those competing at a lower level. Vaulting vertical takeoff velocity seems to be largely independent of isometric force-time characteristics with only a small amount of variance explained by force at 50 ms.